The Urgency of Local Wisdom-Based Population Training for Family Planning Educators - Anindita Dyah Sekarpuri; Bibin Rubini; Soewarto Hardhienata; Handayani Handayani (Journal of Social Research, 2023)
This article aims to discuss the importance of technical training for Family Planning instructors to increase competence in developing Population Data Houses, which is one of the government programs for implementing self-management of population data in rural areas using the local wisdom of silih asih, silih asah, and silih asuh. This research is a quantitative descriptive study carried out in June 2022 with 38 Family Planning Counselor respondents in Bogor Regency, West Java. The results of the research show that the perception of Family Planning instructors regarding local wisdom is at an average of 3.84, which means that the basic capital to be able to form a masagi or perfect character is at a good level, this can be the basic capital to be able to help each other develop themselves in the program training that will be developed in the future for West Java Province Family Planning Counselors. From the results of this assessment, it can be concluded that in the future Population technical training based on local wisdom is necessary for Family Planning instructors by preparing training tools that are appropriate to field conditions.